1981
DOI: 10.1111/j.1399-0039.1981.tb01388.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA antigens and HBV infection: evaluation in the chronic carrier state and in a large family

Abstract: HLA antigens were determined in 65 apparently well chronic carriers of HBsAg, in race-matched controls and in 42 members of a family with a high frequency of hepatitis B virus infection. The only apparent significant association in the chronic carriers was negative, i.e., no HLA-B7 specificities were found among whites. B7 may confer resistance for whites to chronic infection with hepatitis B. In the family neither active (HBsAg) nor prior (anti-HBs) hepatitis B infection was associated with HLA specificities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…The known decrease of the DR3 frequency from the north to the south of Italy has also prompted an analysis of this gene in accord with the geographical origin of our patients; the significant clustering of DR3 on delta-free patients has been confirmed when frequencies were analyzed by geographical subsets. In view of the failure to show clear-cut HLA differences between healthy HBsAg carriers and normal control populations in previous studies (12,13), one may conclude that the HLA imbalances demonstrated in the present study, are linked to the mechanism inducing CALD and do not identify an HLA set-up typical of the HBsAg carrier state. The DR3 gene is a recognized marker of autoimmunity (14) and has been associated with the autoimmune, nonviral variant of CALD (15).…”
Section: Discussioncontrasting
confidence: 78%
“…The known decrease of the DR3 frequency from the north to the south of Italy has also prompted an analysis of this gene in accord with the geographical origin of our patients; the significant clustering of DR3 on delta-free patients has been confirmed when frequencies were analyzed by geographical subsets. In view of the failure to show clear-cut HLA differences between healthy HBsAg carriers and normal control populations in previous studies (12,13), one may conclude that the HLA imbalances demonstrated in the present study, are linked to the mechanism inducing CALD and do not identify an HLA set-up typical of the HBsAg carrier state. The DR3 gene is a recognized marker of autoimmunity (14) and has been associated with the autoimmune, nonviral variant of CALD (15).…”
Section: Discussioncontrasting
confidence: 78%
“…In general, studies of this kind have shown that the spreading and persistence of HBV are more efficient among Asian people than other ethnic groups (9,28,29). To explain this phenomenon, hypotheses have been raised concerning environmental, nutritional and genetic factors, but they are unproved (17,(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…and B8 and Bw3S (Scngar ct al. 1979), although other studies have found no association (Sampliner et al 1981, Majsky et al 1979). These Polynesians were monitored for circulating Hepatitis €3 surface antigen and antibodies to the surface and core antigens.…”
Section: Discussionmentioning
confidence: 76%